Evaluation of bio-efficacy and compatibility of emamectin benzoate with neem based biopesticide against fruit borers of brinjal and okra - ANAND, G K SUJAY; SHARMA, R K; SHANKARGANESH, K (The Indian Journal of Agricultural Sciences, 2014)
Bio-efficacy and physical compatibility of biorational insecticides, viz. emamectin benzoate and Neem Baan® was investigated against brinjal shoot and fruit borer, Leucinodes orbonalis Guenne and okra shoot and fruit borer, Earias vittella Fab. under field conditions during kharif 2010 and 2011. Both biorationals were found compatible with each other by using jar test and emulsion stability. The results revealed that in both brinjal and okra there was no phytotoxicity observed due to emamectin benzoate with Neem Baan® combination. The lowest per cent fruit infestation was observed in the treatment of emamectin benzoate combined with Neem Baan® @ 7 ml per litre of water, i e 7.36% and 5.39% on number basis and 8.13% and 5.77% on weight basis in brinjal during kharif 2010 and 2011 respectively. Also the highest marketable fruit yield in weight basis was also obtained in the treatment (12.35 tonnes/ ha and 16.89 tonnes/ha) during kharif 2010 and 2011. Similarly, in okra also it recorded lowest fruit infestation (5.92% and 5.59%) and highest marketable yield (1.62 tonnes/ha and 2.19 tonnes/ha) in 2010 and 2011 on weight basis. Further, it was observed that the plant parameters like shoot length and number of flowers recorded significantly higher in the treatment of emamectin benzoate combined with Neem Baan® than untreated control (T8) in both the years. The results indicated that the combination of neem formulation with emamectin benzoate was effective in managing L. orbonalis and E. vitella.